Analysis of Clinical Features of Pulmonary TB Patients at Dr. Hospital. P.P. Magretti Saumlaki in 2022 - Anna Lince Dasmasela; Yuly Peristiowati (Journal of Community Engagement in Health, 2024)
Pulmonary Tuberculosis is the most common disease in 2022 at RSUD dr. P.P. Magretti Saumlaki Tanimbar Islands, Maluku. This study aims to determine the clinical picture of patients according to the characteristics of person, place and time. The retrospective approach is presented in descriptive form. The sampling technique uses purposive sampling. The sample was 51 pulmonary TB patients in the isolation room in 2022 with complete medical record files. The research results showed that the largest age group was 19-44 years, 24 people (47.1%). The male gender was more numerous, numbering 28 people (54.9%). The most common clinical symptoms were shortness of breath, 15 people (29.4%); The highest number of supporting examinations with Ro Thorax was 36 people (70.6%). The most common diagnoses were pulmonary TB on OAT as many as 22 people (43.1%). More patients returned home and recovered, namely 17 people (33.3%). The longest length of stay was 21.6% (3 days). The conclusion of this study is that pulmonary TB patients in the isolation room at RSUD dr. P.P. More Magretti in 2022: male gender, age 19-44 years, clinical symptoms of shortness of breath, AP/PA Thorax X-ray examination, discharged home recovered, and 3 days of hospitalization.